2014
DOI: 10.1111/jnc.12660
|View full text |Cite
|
Sign up to set email alerts
|

Profiling the genes affected by pathogenic TDP‐43 in astrocytes

Abstract: Mutation in TAR DNA binding protein 43 (TDP-43) is a causative factor of amyotrophic lateral sclerosis (ALS) and frontotemporal lobar degeneration (FTLD). Neurodegeneration may not require the presence of pathogenic TDP-43 in all types of relevant cells. Rather, expression of pathogenic TDP-43 in neurons or astrocytes alone is sufficient to cause cell-autonomous or non-cell-autonomous neuron death in transgenic rats. How pathogenic TDP-43 in astrocytes causes non-cell-autonomous neuron death, however, is not c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 42 publications
(55 reference statements)
2
26
0
Order By: Relevance
“…CHI3L1 is a multifunctional protein that has been implicated as a critical regulator of anti-infectious and adaptive T helper 2 (Th2) responses (18,24). Using a C. albicans keratitis model, we tested the hypothesis that CHI3L1 plays a role in antifungal responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CHI3L1 is a multifunctional protein that has been implicated as a critical regulator of anti-infectious and adaptive T helper 2 (Th2) responses (18,24). Using a C. albicans keratitis model, we tested the hypothesis that CHI3L1 plays a role in antifungal responses.…”
Section: Discussionmentioning
confidence: 99%
“…CHI3L1 can be readily detected in the circulation of normal individuals. However, its expression is dysregulated in the circulation and/or tissues from patients with a variety of diseases characterized by inflammation and/or tissue remodeling (24). Studies using CHI3L1 knockout mice demonstrated exacerbated inflammation, hemorrhage, and lung injury following Streptococcus pneumoniae infection, indicating the protective role of CHI3L1 in promoting bacterial clearance and augmenting host tolerance (25).…”
mentioning
confidence: 99%
“…Several thousand TDP-43 and FUS RNA-binding sites have been characterized on pre-mRNA molecules, including those involved in splicing functions of long pre-mRNAs essential to neuronal development and integrity [176,182,183]. Alternative splicing of pre-mRNAs was found to be broadly altered in TDP-43 and FUS-related ALS, leading to the dysregulation of normal neuronal gene expression with the synthesis of thousands of aberrantly spliced mRNA molecules [182,[184][185][186][187][188][189]. In particular, these recent transcriptome studies highlighted an alteration of levels and/or splicing of genes involved in RNA processing, synthesis of neurotrophic factors and synaptic function.…”
Section: Tdp-43 and Fus-related Alsmentioning
confidence: 99%
“…Disruption of GEMs is observed in both SMA and TDP-43/FUS-related ALS [191,192], and concordantly, the integrity of spliceosomes was found to be altered in both diseases [121]. Expression level alteration/sequestration of RNAprocessing factors such as RRM-containing splicing factors (hnRNPs, SRSFs) further leads to large splicing alterations in SMA [123][124][125], TDP-43/FUS-related ALS [182,[184][185][186][187][188][189] and C9ORF72-related ALS [153,154].…”
Section: Rna-mediated Mechanisms Of Neurodegenerationmentioning
confidence: 99%
“…It is also unclear how the abnormal astrocytic TDP-43 expression could have contributed to neuronal death, but our patient's case may provide clues as to the mechanism associated with non-cell autonomous neuronal death in ALS. 29 In conclusion, whether the glial (especially astrocytic) accentuation of TDP-43 pathology in patients with p. N345K mutation occurs by chance, or whether the pathogenic mutation causes preferential accumulation of TDP-43 in glia is still not resolved. Further pathological investigations are needed to clarify whether the p.N345K mutation has the potential to accentuate glial TDP-43 pathology.…”
Section: Discussionmentioning
confidence: 96%